Formulation of Gastro Retentive Floating Microballoons of Ciprofloxacin Hydrochloride - Pradeep, Anand; ., Sreeganesan (Asian Journal of Pharmaceutical Research and Development, 2015)
The present study involves formulation of microbaloons of Ciprofloxacin HCL as a model drug for prolongation of Gastric resident time. Ciprofloxacin is a second generation Fluroquinolone having bactericidal activity and is used in the treatment of respiratory, urinary tract, gastrointestinal and abdominal infections including Gram-negative (Escherichia coli) and Gram-positive (Streptococcus pneumonia, Streptococcus pyogenes) bacterial pathogens. Ciprofloxacin HCl with pKa value of 4.9 is a weak acid which will remain unionized at acidic pH thus increases absorption in the stomach region. It is primarily absorbed from the stomach and upper part of intestine. The objective of the study was to formulate the microbaloons which are capable of floating on the gastric fluid and release the drug over a period of 24 hours thus increasing bioavailability and decreasing the frequency of dosage. The compatability of Ciproflocxacin HCl and polymers is studied by IR spectroscopy and DSC methods. Microbaloons were formulated by Emulsion solvent diffusion methods using polymers like Eudragit RS100 and Eudragit RL100 in various ratios.